The Importance of College Guidance and Choosing Schools and Majors under China’s New College Entrance Examination Policy - Su, Linghong (Transactions on Social Science, Education and Humanities Research, 2024)
Under the reform policy of the New College Entrance Examination (NCE), students’ choices are increased and at the same time, their ability to make choices is also challenged. Under the plurality of the system of higher education, whether the parents’ education and social status will affect the news that students get and thus the choice of higher education. Nowadays, the number of research in China is relatively small, and most of the research vision is oriented to university education, with insufficient attention paid to the level of high school education. The systematic research related to it is almost in a blank condition, and the practical projects generally lack large-scale popularization, and the problems exposed in the interface between high school education and university education are numerous. There is very little cooperation between them, which is relatively neglected at the levels of school, society and family. Schools, society, families and other levels have been neglected. This paper will explore the reform of college guidance under the new college entrance examination policy, its impact and suggestions. High school education should be closely related to university education. In the face of the gap in information about university education, it is important for schools to improve the number and quality of teachers. The government should increase regulation of paid college counseling and shut down poor-quality counseling agencies.